Hypothyroid Symptoms in Levothyroxine-Treated Patients - Maisha Freeman; Georges A. Adunlin; Candice Mercadel; Sara Danzi; Irwin Klein (University of Minnesota Libraries Publishing, 2019)
Purpose: Approximately 15% of patients with hypothyroidism are dissatisfied with their treatment due to persistence of residual symptoms associated with hypothyroidism.  The purpose of this study was to compare thyroid symptoms using the hypothyroid symptom scale (HSS) in patients receiving stable thyroid therapy for 6 months to patients without hypothyroidism.  The HSS was used to identify the percentage of levothyroxine-treated hypothyroid patients with residual or persistent hypothyroid symptoms. Methods:  Patients included in the study had hypothyroidism and were receiving a stable/maintenance dose of levothyroxine sodium therapy, unchanged for at least 6 months.  A control group of patients were included if they did not have an active prescription for thyroid hormone therapy.  The HSS was administered via phone or face-to-face interactions.   Patients were asked to score 10 symptoms over the past month on a scale of 0 to 4 (e.g., 0, absence of, to 4, severe symptoms).  Results were analyzed using descriptive and inferential statistics.  T-tests and chi-squared analysis were used to assess differences in continuous and categorical variables. Results:  A total of 68% of the contacted patients responded to the survey.  A total of 302 patients were in the intervention group and 273 were in the control group.  The mean total HSS scores between groups were significantly higher in the treatment compared to the control group (13.92 ± 10.91 vs.10.07 ± 7.85; P < 0.001). Conclusion: Significantly more patients receiving thyroid hormone therapy experienced residual thyroid symptoms compared to control patients.  Attempts should be made to offer alternatives for hypothyroid patients with persistent symptoms.   Article Type: Original Research